2022
DOI: 10.3390/nu14030698
|View full text |Cite
|
Sign up to set email alerts
|

Medical Nutrition Therapy in Diabetes Mellitus: New Insights to an Old Problem

Abstract: The management of all types of diabetes mellitus (DM) has transformed during the past decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
0
0
Order By: Relevance
“…The latter may indeed help to preserve SMM and improve blood glucose responsiveness ( 46 ). Our findings are compatible with an earlier study by Grammatikopoulou et al on how an appropriate medical nutrition therapy has an important role in treating diabetic patients both prediabetes, gestational diabetes and T2DM ( 47 ). A possible mechanism of lowering HbA1c through PMB use could be via optimal energy, carbohydrate, protein and fat intake ( 48 ).…”
Section: Discussionsupporting
confidence: 93%
“…The latter may indeed help to preserve SMM and improve blood glucose responsiveness ( 46 ). Our findings are compatible with an earlier study by Grammatikopoulou et al on how an appropriate medical nutrition therapy has an important role in treating diabetic patients both prediabetes, gestational diabetes and T2DM ( 47 ). A possible mechanism of lowering HbA1c through PMB use could be via optimal energy, carbohydrate, protein and fat intake ( 48 ).…”
Section: Discussionsupporting
confidence: 93%
“…Medical nutrition therapy (MNT), as an integral part of all diabetes care and management, is known to be cost effective (3) . Nutrition education is a segment of the MNT for patients with diabetes, and the delivery of nutritional education is believed to be a priority for improvement in T2DM treatment outcomes (4) . Moreover, pieces of evidence have shown that nutrition education can effectively reduce disability and mortality caused by diabetes (5) .…”
mentioning
confidence: 99%